Книга як комунікаційний інструмент: потенціал читацьких можливостей - Антоник, Ольга (Видавництво Львівської політехніки, 2020)
Conceptual bases of the book interpretation as a social-communicative phenomenon and a publishing product have been given. The point concerns the interrelation of the edition culture and culture of reading; it’s about evolution of book edition communicative potential as unity of the content, art-image and printing implementation.
Keywords: книга; читач; культура видання; комунікаційний канал; суб’єкт комунікації